Identification of Candidate Biomarkers for Salt Sensitivity of Blood Pressure by Integrated Bioinformatics Analysis - Chen, Chen; Liu, Guan-Zhi; Liao, Yue-Yuan; Chu, Chao; Zheng, Wen-Ling; Wang, Yang; Hu, Jia-Wen; Ma, Qiong; Wang, Ke-Ke; Yan, Yu; Yuan, Yue; Mu, Jian-Jun (Frontiers in Genetics, 2020)
In current study, we aimed to identify potential biomarkers for salt sensitivity of blood pressure (SSBP) which may provide a novel insight on the pathogenic mechanisms of salt sensitive hypertension. Firstly, we conducted weighted gene co-expression network analysis (WGCNA) and selected a gene module and 60 hub genes significantly correlated to salt sensitivity of blood pressure. Then, GO function and KEGG signaling pathway enrichment analysis as well as protein-protein interaction network analysis were performed. Furthermore, we identified a 5-gene signature with high connectivity degree in PPI network and high AUC of ROC curves which may have high diagnosis value for salt sensitivity of blood pressure. Moreover, through combining two gene screening methods, we identified 23 differentially expressed circRNAs and selected top 5% circRNAs (1 circRNA) with the highest connectivity degree in the co-expression network as hub circRNA highly associated with salt sensitivity of blood pressure. Finally, we carried out RT-qPCR to validate the expression of 5 hub genes and our results showed that the expression of HECTD1 (P=0.017), SRSF5 (P=0.003), SRSF1 (P=0.006), HERC2 (P=0.004), TNPO1 (P=0.002) were significantly up-regulated in the renal tissue in salt sensitive rats compared to salt resistant rats, indicating that these 5 hub genes can serve as potential biomarkers for salt sensitivity of blood pressure.